Effect of gold mining on total factor productivity of farmers: Evidence from Ghana - John K. M. KUWORNU; Yaw B. OSEI-ASARE; Michael O. ANSAH; Akwasi MENSAH-BONSU (Acta Agriculturae Slovenica, 2018)
Gold mining comes with several benefits to developing countries, manifested mainly in the form of employment and revenue, but simultaneously impacts negatively on the immediate environment. It affects the economic structure including agriculture and its productivity. Hence, this study investigated the effect of gold mining on total factor productivity of farmers in Ghana using 110 cocoa farmers from Asutifi North and Asutifi South districts of the Brong Ahafo Region, categorised into mining and non-mining areas respectively. About 83 % of the farmers in the mining areas were affected by gold mining through channels such as land disputes, relocation of farm/residence, high cost of labour, illegal small-scale mining and dust settlement on crops. Also, about 64 % of cocoa farmers in the mining areas lost their farm lands (between 0.4 and 3.64 ha as a result of gold mining. The Tornqvist Total Factor Productivity (TFP) indices for cocoa farmers in the non-mining areas (mean TFP of 1.404) were also statistically higher than those in the mining areas (mean TFP of 0.371). The study concluded that gold mining activities adversely affect productivity of farmers in the catchment areas. The study recommends, among others, that a policy of land-for-land should be in place and effectively implemented to ensure that mining companies in order to enhance and ensure continuity of livelihoods must fully replace lands lost through mining activities.